A hermenêutica do bem viver : sensibilização, solidariedade e abertura interdisciplinar - Souza, Roberto Wagner Xavier de (2019)
The overall objective of this research is the delineation and analysis of how the Hermeneutics of Good Living, a theoretical foundation (dialectical conjunction) backed by the ideas of concrete constitutional hermeneutics, diatopic hermeneutics and Gadamerian philosophical hermeneutics, could provide an interdisciplinary path and concretist socioenvironmental hermeneutic opening that assists in the solution of environmental conflicts. As specific objectives: i) propose the affirmation of the environmental sense as a way of overcoming the normative aspect of crises and paradigmatic transitions about Nature, in an interdisciplinary and dialogical way; ii) discuss a re-reading of intergenerational environmental solidarity (from ancestral generations to future generations) with its binding and axiological aspect; iii) to analyze the foundations of Good Living as an alternative proposal for development that is based on the anthropocentric paradigm. It is an exploratory-theoretical (fundamental) research, for emphasizing the discovery of ideas and insights, developed through the procedure and bibliographic method of data collection in written materials and the method of classical deductive-dialectical approach, with an interdisciplinary character, using elements of legal and philosophical hermeneutics as well as ethics, culture and politics. The results show that environmental sensibility is a way of overcoming the prevalence of an instrumental vision, or simple conflict, in the face of diverse conceptions of nature, emphasize the active involvement of civil society to the powers constituted by means of consensuses that legitimize a factual assumption and to provoke the establishment of the environmental sense, triggering degrees of responsibility and commitment. Therefore, a reinterpretation of intergenerational environmental solidarity and hermeneutical conjunction, based on cultural, ecological, political and normative convergence, is presented in a way that supports a new conception that reinvigorates the socio-juridical and environmental paradigm in the configuration of the socio-environmental State of Law. As a theoretical and conciliatory model the Hermeneutics of Good Living brings a concretist posture that can better articulate among the actors involved with the environmental theme: state, non-state and several segments that participate in the formulation and implementation of public policies.